Using Literature Review to Inform an Anti-Oppressive Approach to Community Safety - Chamberlain, Julie; Cardigan Smith, Stacy; Perrott, Dagen (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2024)
Literature review is a common piece of any scholarly research, but it is rare for it to be squarely at the centre of a community-based project. In this Report from the Field, the research team critically reflects upon the creation and use of a literature review on grassroots, anti-oppressive approaches to community safety in Winnipeg, Manitoba, Canada. Writing in conversation with one another, we explore the tensions of navigating and challenging safety discourse and securitization practices in our city, from our distinct experiences and positions as an academic researcher, community partner, and student research assistant. In the process, we illuminate a collaboration that offers insights for academic and community researchers alike. We reflect on creating an accessible basis for community conversation and planning while doing justice to the sources of anti-oppressive theory and practice, particularly when initially speaking to mostly white and privileged community members. The literature review has generated discussion about what it means to approach safety as a collective resource rather than an exclusive possession, and will inform practical strategies in the neighbourhood and beyond.